Dual channel double wavelength method in optical fiber-based gas sensor for carbon dioxide detection - Razali, Muda; Norhana, Arsad; Nur Hazliza, Ariffin; Amran, Abdul Hadi (UTeM, 2018)
A novel double wavelength strategy in optical fiberbased sensor for detection of carbon dioxide (CO2) gas is presented. The detection strategy works based on an open-path direct absorption spectroscopy in the mid-infrared (mid-IR) wavelength range. The sensor system comprises of a broadband filament emitter acting as the Infrared (IR) light source, Chalcogenide Infrared (CIR) Optical Fibers, two Pyroelectric detectors which been fitted built- in with a limited bandpass CO2 channel and a reference channel. The sensor additionally uses calcium fluoride (CaF2) limit bandpass (NBP) channel for recognition of CO2 gas without cross-sensitivity to different gasses exist in the surrounding environment. The correlation amongst test and computed sensor yields are additionally exhibited.